Penambahan Daun Bambu ke dalam Kertas HVS Bekas untuk Membuat Kertas Daur Ulang di Kecamatan Pengasih, Kabupaten Kulon Progo - Kenwari Hawa; Abdul Hadi Kadarusno; Haryono Haryono (Poltekkes Kemenkes Yogyakarta, 2015)
Some people in Sidomulyo Village of Kecamatan Pengasih work to make handicrafts made ofapus bamboo. Parts of bamboos which are not used have not yet been utilized and just become waste. The bamboo leaves which are containing 46,24 % cellulose can be utilized as additional material for recycling paper making. The aim of study was to know whether the recycledpapers produced from three mixture formulas of used HVS paper and apus bambo leaves havedifferent tensile strength, by conducting an experiment with post test only control group design.From five replications, it was known that the average paper tensile strength yielded from formula I (400 ml used HVS paper and 600 ml bamboo leaves) was 0,160 N/mm; from formula II (200ml used HVS paper and 800 ml bamboo leaves) was 0,320 N/mm; from formula III (1000 mlbamboo leaves) was 0,386 N/mm; and from control (1000 ml used HVS paper) was 0,106 N/mm. The statistical analysis results from independent t-test and Kruskal-Wallis test at 95 %confidence level showed that those differences were significant, except between the controland the papers produced from formula I, and between formula II and formula III. It can be concluded that the more the apus bamboo were added the more the tensile strength will be obtained. Nonetheless, the best paper tensile strength in this study still lower than that of factorymade carton paper i.e. 6,920 N/mm.